2021
DOI: 10.1016/j.jtumed.2021.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Lip and oral cavity cancers (C00-C06) from a mega city of Pakistan: Ten-year data from the Dow Cancer Registry

Abstract: Objective The objective of this report is to provide an overview of lip and oral cavity cancer in Karachi, the largest city in Pakistan. Methods This study was undertaken at the Dow Cancer Registry. During 2010–2019, all patients who were residents of Karachi who had been diagnosed with lip and oral cavity cancer were registered and recruited for this study. The data were entered in SPSS and MS Excel sheets to investigate frequencies, age-standardized-rates (ASR) and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Oral cavity cancer is one of the leading causes of cancer-related death in South Central Asia, including Pakistan. It is the first and second most common cancer in Pakistani males and females, respectively, and has the second-highest rate of oral cavity cancers worldwide, thus continuing to be a major public health crisis and a significant hurdle in improving life expectancy [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral cavity cancer is one of the leading causes of cancer-related death in South Central Asia, including Pakistan. It is the first and second most common cancer in Pakistani males and females, respectively, and has the second-highest rate of oral cavity cancers worldwide, thus continuing to be a major public health crisis and a significant hurdle in improving life expectancy [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral cavity cancer is one of the leading causes of cancerrelated death in South Central Asia, including Pakistan. It is the first and second most common cancer in Pakistani males and females, respectively, and has the second-highest rate of oral cavity cancers worldwide, thus continuing to be a major public health crisis and a significant hurdle in improving life expectancy [1,2]. e rationale for the high incidence of oral cavity cancers in Pakistan, and South Asia in general, is the frequent, persistent, and prevalent use of substances classified as oral cancer risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Oral Squamous cell carcinoma remains nevertheless one of the greatest widespread tumors globally and [15][16][17][18][19] the second most common tumor in Pakistan. It is of immense significance to be a consistent diagnostic and prognostic biomarker for cancer patients to be able to make available indispensable information for attaining a clinical conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, mucins have been contemplated as prospective biomarkers in cancer diagnosis attributable to their distinctive representation in cancer patients as contrasted to the normal one. Among MUC4 is considered a [15][16][17][18] promising one.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 According to histological grading, majority of OSCC patients were moderately differentiated (67.7%), while poorly differentiated and well differentiated were 16.6% and 15.7%, respectively. 9 Another study in Karachi revealed the moderately differentiated cancer (grade II) to be the commonest (59%), followed by well differentiated grade I (36%) and poorly differentiated grade III (5%). The clinical staging revealed 52% subjects involved in stage III/1V cancer.…”
Section: Introductionmentioning
confidence: 98%